Beyond Real and Fake: A Hybrid Visual Authenticity Framework for Generative AI in Creative and Media Ecosystems - Moh. Ali Wisudawan Prakarsa; Aliyah Aliyah; Heri Wijayanto; Zulfah Hasanah; Widya Octary Setiawardhani (INSPIRETECH GLOBAL INSIGHT, 2026)
The emergence of generative artificial intelligence has radically transformed the production, dissemination, and interpretation of visual media, precipitating a crisis of confidence regarding visual authenticity—a concept historically predicated upon the indexical nature of photography. This research investigates the reconfiguration of visual authenticity within photography, illustration, and packaging design in the age of generative AI, identifying cross-domain thematic regularities to develop a conceptual model of